The first record of the family Chloroperlidae (Plecoptera) from the Guangxi Zhuang Autonomous Region of southern China, with description of a new species of Sweltsa Ricker, 1943 - Mo, Raorao; Ye, Jianping; Wang, Guoquan; Li, Weihai (Zootaxa, 2020)
The family Chloroperlidae is reported from Guangxi Zhuang Autonomous Region of southern China for the first time with a description of a new species of the genus Sweltsa, S. bilobata sp. nov. The new species is compared to two similar species.